Retirement choice simulation in household settings with heterogeneous pension plans - Jinjing Li; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2011)
This paper estimates a structured life cycle model of family retirement decision using a unique historical dataset back simulated from Living in Ireland survey. Our model takes the advantages of the dataset and models retirement decisions in terms of monetary and leisure incentives, which reflect the complex welfare system in Ireland. The household extension version of the model adapts a collective modelling approach, where the intra-household bargaining is considered. We further incorporate complimentary leisure, which allows us to analyse the interactions of spouses' retirement timing. This methodology enables us to capture the dynamics of retirement and tax-benefit policies and can be used to simulate the effect of policy reform on household retirement behaviours. The paper, in addition, applies the model to assess individual budgetary implications and the labour market impact of rising the minimum retirement age. Our simulation shows that increasing the minimum age for state pension entitlement to 70 would only delay the retirement by less than 2 years according to the individual based model. When we consider the intra-household bargaining and the higher preference of leisure found in the dual career households, the effect of postponing retirement further declines. The result suggests barely postponing the minimum retirement age for state pension without redefining the occupation and private pension rules will only have limited impact for household retirement behaviour in Ireland.
urn:nbn:de:101:1-201108092933
Keywords: J14; J26; 330; retirement; choice modelling; microsimulation